Bridging worlds: ethnic minority pupils in Catholic schools in England - Morris, Andrew B. (Journal of beliefs and values, 2010)
Aggregated attainment data for each of the four Key Stages of the National Curriculum during 2006-07 are used to compare the performance of schools having differing proportions of ethnic minority pupils on roll. The data are for all maintained primary and secondary schools that completed the 2007 Annual Schools’ Census. There are noticeable differences across the phases between schools in the Catholic and non‐Catholic sectors. The average levels of pupil attainment in Catholic schools tend to be higher than in other institutions, the differentials between the sectors increasing the greater the proportion of ethnic minority pupils on roll. The significance and limitations of the findings are discussed and areas for further study suggested.